MANAJEMEN DAN PENDAPATAN USAHA KERAMBA JARING APUNG (KJA) DI NEGERI AMAHAI DAN KELURAHAN LESANE KABUPATEN MALUKU TENGAH - Agustina Baulu; Lilian Matilda Soukotta; Dionisius Bawole (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2017)
Floating Net cage (KJA) is a fish cage which usually made of wood, bamboo, or iron and buoys with anchoring system. In Central Maluku District, the areas that potential in the development of cultivation KJA is Amahai and Lesane. The objectives of this research are: 1) To describe the application of business management function of KJA in Amahai and Lesane Sub-district and 2) to analyze income obtained in KJA business in Amahai and Lesane Sub-district. The method used is descriptive method. The results show that the cultivation business with KJA system in Amahai and Lesane villages took place twice a year by maintaining different types of fish. The group Wairano I and Wairano II maintaining the tiger grouper (Epinephelus fuscoguttatus), Beronang (Siganus) and Kuwe (Cranx sp), while Kura-kura and Kuda Laut maintains the species Tiger Grouper (Epinephelus fuscoguttatus) and Rat Grouper (Cromileptes altives). The application of management functions in the floating net cage business (KJA) in Amahai and Lesane districts is almost similar in implementing the planning and direction functions, but different in organizing and coordinating functions.